2022
DOI: 10.1016/j.jaip.2021.10.067
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic–Related Reductions in Pediatric Asthma Exacerbations Corresponded with an Overall Decrease in Respiratory Viral Infections

Abstract: What is already known about this topic? Although respiratory viruses, air pollutants, and aeroallergens are implicated in worsening pediatric asthma symptoms, the interplay between these factors and asthma exacerbations is not well understood. Asthma exacerbations decreased significantly during the coronavirus disease 2019 pandemic, allowing for the investigation of these asthma triggers relative to asthma activity.What does this article add to our knowledge? The sustained reductions in viral infections and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…In support of this hypothesis, Gujon et al 15 in California confirmed a correlation between the reduction in ED visits for asthma exacerbation and the reduction in particulate matter as well as in viral infections 15 . Differently, Sayed et al 24 in Philadelphia did not observe changes in the rate of air pollution and in the environmental aeroallergens during the pandemic compared with previous seasonal data, while they highlighted a significant reduction of viral infections including RSV, Rhinovirus, Influenza A and B.…”
Section: Discussionmentioning
confidence: 84%
“…In support of this hypothesis, Gujon et al 15 in California confirmed a correlation between the reduction in ED visits for asthma exacerbation and the reduction in particulate matter as well as in viral infections 15 . Differently, Sayed et al 24 in Philadelphia did not observe changes in the rate of air pollution and in the environmental aeroallergens during the pandemic compared with previous seasonal data, while they highlighted a significant reduction of viral infections including RSV, Rhinovirus, Influenza A and B.…”
Section: Discussionmentioning
confidence: 84%
“…21 Viral infections are the main triggers of asthma exacerbations in all age groups. 13,22 All over the world, there is a growing body of evidence regarding the reduction during the pandemic of health care utilization for asthma, [23][24][25][26][27][28][29][30][31][32][33] and reductions in hospital admissions for seasonal respiratory diseases (upper airway infections, bronchiolitis, and pneumonia) were widely recorded. 3,7,9,10,20,34,35 In addition, the decrease in recorded air pollutants must be considered, because exposure to air pollution is one of the external triggers for the onset of asthma, particularly in larger cities.…”
Section: Discussionmentioning
confidence: 99%
“…After stratification, during the regular prevention period, only the weekly visits of adults increased significantly compared with lockdown period. Previous studies have focused on the impact of the COVID-19 lockdown on health care utilization for asthma, and mostly focus on children [ 17 , 18 , 19 , 20 , 21 , 22 ]. For example, a cross-sectional study from Guangzhou (China) reported that the number of hospitalized children with severe asthma exacerbation decreased under the implementation of strict countermeasures for COVID-19 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional study from Guangzhou (China) reported that the number of hospitalized children with severe asthma exacerbation decreased under the implementation of strict countermeasures for COVID-19 [ 17 ]. Two related studies in Philadelphia, USA, also focused only on childhood asthma [ 18 , 19 ]. Although a study in the UK covered people of all ages, it only analyzed the impact of lockdown on asthma-related health care utilization, without further stratification by adults and children [ 20 ].…”
Section: Discussionmentioning
confidence: 99%